On developing the RTB toolbox. RTB workshop cluster CC2.1 phase 2. - Kilwinger, Fleur B.M.; Pircher, T.; Almekinders, Conny J.M.; Andrade-Piedra, J.L.; McEwan, M. (2017)
Twenty-six participants (nine women), members of the RTB cross-cutting cluster 2.1. on “Quality Seeds and Access to Improved Varieties” met between 8-13th May 2017, in Lunteren and Wageningen, the Netherlands. The workshop participants were from: Bioversity, CIAT, CIP, IITA, UF, and WUR. The participants discussed the idea of the RTB crop seed systems tool box: what it should do, what it would eventually look like, and who would use it. Most importantly there was debate on how to arrive at having a toolbox with methods and tools that can be applied to understand, diagnose, intervene and evaluate RTB crop seed systems. Existing and novel methods and tools will be applied in different crop and country contexts during RTB 2.0 to adapt and fine tune the tools. It is envisioned that, applications of the methods and tools in two or more seed systems will enable an improved characterisation and understanding of the interactions among socio-economic and natural-technical phenomena of seed system performance, comparison between seed systems, and more effective RTB crop seed system interventions. During the week, participants reviewed research questions they had identified for the seed systems and seed interventions they worked on, and research methods to collect the data for answering the research questions. There were many shared research questions, predominantly relating to the interface of formal and informal seed systems and to seed degeneration.